High-strength complex-phase hot-rolled wire rod for 2500 MPa bridge cable and manufacturing method of high-strength complex-phase hot-rolled wire rod
Through the design of Nb-V-Mo chemical composition and the on-line molten salt end quenching toughening technology, the problem of strong plastic matching and insufficient tissue uniformity of hot-rolled strips for 2500MPa-level bridge cables is solved, and the control of material costs and the improvement of production efficiency is achieved, while reducing the risk of wire breakage.
Patent Information
- Application Number
- CN202510423317.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-07
AI Technical Summary
The prior art is difficult to effectively improve the strong plastic matching and structural uniformity of hot-rolled strips for 2500MPa-level bridge cables, while controlling material costs and improving production efficiency, and there is a challenge of risk of wire breaking.
The high-carbon chemical composition design of Nb-V-Mo and combined with the online molten salt end quenching and toughening technology, the soxunitite phase zone is quickly entered from the high-temperature austenite state through ultra-high cooling speed, and the short-term phase change and isothermal phase change are carried out to control the precipitation and growth of carbides. Finally, the hot-rolled strips of complex phase structure are prepared by slow cooling of the rollers.
It significantly improves the strong plastic matching and tissue uniformity of hot-rolled strips, reduces material costs and production energy consumption, reduces the risk of wire breaking, and improves the tensile strength and cross-section shrinkage rate of the product.
Smart Images

Figure CN119913346A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot-rolled wire rods, and specifically relates to a high-strength multi-phase hot-rolled wire rod for 2500MPa-level bridge cables and a manufacturing method thereof. Background Art
[0002] Ferrite matrix cold-drawn pearlite steel is widely used in the fields of wire ropes, bridge cables, stranded wires, piano wires, etc. due to its good toughness and suitability for large deformation drawing. With the rapid development of large-span bridges, the strength grade of cold-drawn pearlite hot-rolled wire rod parent material for bridge cables has also been continuously improved. However, since cold-drawn pearlite steel is a ferrite matrix, its strength level is often lower than that of steel with shear phase transformation structure. In order to meet the requirements of bridge cable steel to bear loads and lightweight in large-span bridge structures, it is also necessary to develop a high-strength hot-rolled wire rod to adapt to the production of 2500MPa bridge cables.
[0003] The existing high-strength bridge cable hot-rolled wire rod mainly adopts Stelmor air-cooled and line-controlled high-carbon cold-drawn pearlite steel. The following technical difficulties exist in manufacturing high-strength and plasticity-matched 2500MPa grade bridge cable hot-rolled wire rod: 1. The improvement of the strength grade of the base material of hot-rolled wire rod is often achieved by increasing the content of carbon and alloying elements. The strength of cold-drawn pearlite steel is lower than that of steel with shear phase transformation structure, and more carbon and alloying elements need to be added. However, more carbon and alloying elements will also increase the control risk of wire rod deterioration structure. The main reasons are: on the one hand, after the carbon content of cold-drawn pearlite steel exceeds the eutectic point of 0.77%, the maximum cooling capacity of the Stelmor air-cooling line is limited, and the wire rod spends a long time in the secondary cementite precipitation temperature range. With the influence of carbon content and segregation, the network carbide precipitation range continues to increase, resulting in a certain degree of strength and plasticity deterioration in cold-drawn pearlite steel. Although carbon is an effective strengthening element, improper use and control will also cause wire breakage problems in downstream cold drawing and subsequent processing of steel; on the other hand, in order to minimize the level of network carbides, strong air cooling treatment will be used after wire drawing, but the air cooling line The influence of cooling control ability and uncontrollability will further increase the temperature difference from the surface to the core of the wire rod. As the alloy element content of the wire rod increases, the influence of the hardenability and segregation of alloy elements on the wire rod increases. Some overcooling positions are more likely to form uncontrollable hard and brittle structures such as bainite and martensite. Reducing the carbon content requires further increasing the content of alloy elements. For example, patent CN110055392B discloses a high-toughness bridge cable steel with a tensile strength ≥2500Mpa and a preparation method thereof, which adopts a low-carbon composition design of C-Mn-Al-V and a high alloy element content. This not only brings about the problem of high material cost, but also further increases the difficulty of controlling the deteriorated structure. The deteriorated structure will increase the brittleness of the structure and the fluctuation of mechanical properties. As the wire rod continues to cool and undergo phase transformation, the wire rod is already in a low-temperature state after the phase transformation is incubated. There is a large stress in the wire rod structure, which affects the plasticity and uniformity of the wire rod, thereby increasing the risk of wire breakage during downstream cold drawing and subsequent processing.
[0004] 2. In order to improve the strength and drawing performance of wire rods, existing high-strength wire rods for bridge cables will choose to increase the content of carbon and alloy elements, improve the hardenability of steel, reduce the critical cooling rate of steel, and obtain fine pearlite structure, namely sorbite structure. However, on the one hand, the minimum cooling capacity of the Stelmore air-cooled line is limited, and the time for the wire rod to pass through the phase transformation interval is short, which will affect the sufficient phase transformation of the sorbite, and thus affect the strength of the matrix. The residual austenite is also prone to continue to form abnormal structure in the subsequent cooling process. Increasing the spinning temperature will also significantly extend the online time of the wire rod, affecting production efficiency. On the other hand, the wire rod is in a low-temperature state after continuous cooling phase transformation, and has a large tissue stress in the wire rod, which will increase the fluctuation of mechanical properties, affect the plasticity of the wire rod, and thus increase the risk of wire breakage in the subsequent drawing process.
[0005] 3. Although wire rod can strengthen the matrix through microalloying elements such as Nb, V, and Ti, the cost of microalloying elements is relatively high, and excessive addition is not conducive to material cost. At the same time, it is limited by the cooling control capacity of the Stelmor air-cooling line. The wire rod is affected by the temperature difference between the surface and the core and continuous cooling, and the precipitation driving force is relatively small, resulting in a decrease in the number of precipitated phases, an increase in size, a weakened contribution to strength, and even the formation of relatively large precipitated phases, which affects the material properties. Summary of the invention
[0006] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a high-strength multi-phase hot-rolled wire rod for 2500MPa-level bridge cables and a manufacturing method thereof, which can improve the strength-plasticity matching and organizational uniformity of the wire rod, control material costs, and improve production efficiency. It is suitable for the production of 2500MPa-level bridge cables and is beneficial to reducing the risk of wire breakage during downstream cold drawing and subsequent processing.
[0007] The technical solution adopted by the present invention to solve its technical problem is: A method for manufacturing a 2500MPa high-strength multiphase hot-rolled wire rod for bridge cables, the manufacturing method comprising: The hot-rolled wire rod is rolled to produce a wire rod according to its chemical composition, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.95% to 0.98%, Si: 1.05% to 1.25%, Mn: 0.65% to 0.85%, Cr: 0.40% to 0.60%, Nb: 0.04% to 0.048%, V: 0.035% to 0.045%, Mo: 0.40% to 0.50%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable Impurities; After the wire is spun into a wire rod at a spinning temperature of ≥925°C, it is subjected to an online molten salt terminal quenching and toughening treatment, so that the wire rod first passes through the front section of molten salt and is cooled at a cooling rate of ≥38°C / s, and part of the austenite structure is transformed into quenched martensite, and then is heated to the bainite phase region temperature through the rear section of molten salt, and the untransformed austenite is controlled to be transformed into bainite and isothermally tempered, and the precipitation and growth of carbides are controlled, and finally it is slowly cooled through a roller to be made into a hot-rolled wire rod with a microstructure including a complex phase structure composed of tempered martensite and tempered bainite.
[0008] The design basis of the chemical composition and mass percentage of the above hot rolled wire rod includes: (1) Carbon: The carbon element is an effective carbide strengthening element and austenite forming element with a relatively low price. With the increase of carbon content, it can produce solid solution strengthening effect, reduce the austenite transformation temperature, reduce the martensite transformation temperature, promote short-time quenching by rapid cooling during the front-stage molten salt treatment, increase the tempered martensite content in the organization, affect the morphology and distribution of cementite in troostite, and help to obtain fine and uniform troostite organization during the rear-stage molten salt treatment, thereby improving the material strength. However, excessive carbon content will increase the carbon segregation tendency during the solidification process of the steel billet, increase the control of network carbides and isothermal tempering, and affect the plasticity and toughness of the material and the control of carbide precipitation. Therefore, in order to improve the strength of the hot-rolled wire rod base material, control material costs, and facilitate the control of complex phase organization and carbide precipitation, the mass percentage of C is controlled to be 0.95%~0.98%.
[0009] (2) Silicon: Si is the main deoxidizing element in steel. It can inhibit the coarsening of grains during the front-end molten salt treatment, promote the uniform transformation of quenched martensite, and make the cementite lamellae in the molten salt treatment finer and more uniform during the troostite phase transformation process, so that the tempered martensite maintains a high hardness and strength. However, too high a silicon content will increase the surface decarburization tendency of the steel, prolong the time required for phase transformation incubation, reduce the toughness of the steel, and be detrimental to the control of carbide precipitation and rapid production. Therefore, in order to refine the grains, improve the uniformity and strength of the multiphase structure, and facilitate rapid production, the mass percentage of Si is controlled to be 1.05%~1.25%.
[0010] (3) Manganese: As an austenite-forming element, Mn can increase the hardenability of wire rod, reduce the critical cooling rate of steel, make it easier for steel to form martensite during cooling, promote sorbite phase transformation, and increase the strength of sorbite, which is beneficial to improve the tensile strength of wire rod. However, when the Mn content is too high, it will aggravate the segregation of alloy elements, reduce the activity of carbon, increase the difficulty of isothermal tempering stress relief, and be unfavorable for the subsequent molten salt treatment while controlling the precipitation of carbides, thereby reducing the toughness and plasticity of steel. Therefore, in order to facilitate the control of the complex phase structure of hot-rolled wire rod, reduce the difficulty of structural uniformity and short-time tempering control, and facilitate rapid production, the mass percentage of Mn is controlled to be 0.65%~0.85%.
[0011] (4) Chromium: The Cr element can improve the hardenability of steel, allowing the steel to quickly form a higher proportion of quenched martensite during the short-term quenching in the molten salt in the front stage, and at the same time enhance the stability of austenite. In the latter molten salt treatment process, it can reduce the phase transition temperature, refine the pearlite and cementite lamellae, improve the strength of the troostite, and reduce the strength loss in the subsequent hot-dip galvanizing process of steel wire. However, too high Cr content will aggravate the component segregation, increase the difficulty of controlling the uniformity of the organization and the improvement of plasticity, and the coarsening of carbides will reduce the toughness of the steel, thereby affecting the wire drawing and torsion properties of the steel wire. Therefore, in order to facilitate the complex phase organization, plasticity control and rapid production, the mass percentage of Cr is controlled to be 0.40%~0.60%.
[0012] (5) Niobium: As a microalloying element, Nb can effectively inhibit the grain coarsening of the wire rod during the rolling process by combining with V for precipitation, preventing the growth of austenite grains, improving the strength and toughness of the matrix, and providing more grain boundaries as nucleation sites for martensite, making martensite transformation easier. Niobium carbonitrides will disperse and precipitate during the online molten salt end quenching and toughening process, producing a precipitation strengthening effect, which can further improve the strength of the wire rod. However, the cost of Nb is relatively high. Based on the role of Nb and cost considerations, the Nb content is controlled at 0.04%~0.048%.
[0013] (6) Vanadium: As a microalloying element, V can be dispersed and precipitated during the online molten salt end quenching and toughening process, providing a strong precipitation strengthening effect, thereby improving the strength level of the hot-rolled wire rod without reducing the plasticity. However, the cost of V is relatively high. Excessive addition is not conducive to controlling the cost of the wire rod and has the risk of coarsening. Based on the role of V and cost considerations, the V content is controlled at 0.035%~0.045%.
[0014] (7) Molybdenum: Mo can improve the hardenability of steel and promote the short-term acquisition of most quenched martensite in the front molten salt treatment process. At the same time, it can effectively inhibit the coarsening of strengthening phases such as cementite, Cr, Nb and V precipitation phases, and prevent the coarsening of precipitation phases during the online molten salt end quenching and toughening process, thereby reducing the plasticity of the wire rod. However, the cost of Mo is relatively high, and excessive addition is not conducive to controlling the cost of wire rod. Based on the role of Mo and cost considerations, the Mo content is controlled at 0.40%~0.50%.
[0015] (8) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is ≤ 0.015%.
[0016] The above-mentioned hot-rolled wire rod adopts the high carbon component design of Nb-V-Mo, optimizes the ratio of Si, Mn and Cr, regulates the hardenability of the wire rod, the temperature range of martensite and troostite phase transformation, and provides favorable conditions for obtaining fine quenched martensite, troostite phase transformation and tempering of complex phase structure for martensite short-time phase transformation, while controlling the dispersion and precipitation strengthening of carbides and being able to quickly go offline. On this basis, an appropriate spinning temperature is selected to avoid the spinning temperature being too low to limit rolling control, form network carbides in the spinning stage, promote uniform and fine austenite, and provide favorable conditions for the subsequent molten salt end quenching to promote short-time martensite phase transformation at a higher temperature. The wire rod after spinning passes through the molten salt without air cooling, and undergoes online molten salt end quenching and toughening treatment: 1. Compared with the situation that the deteriorated structures such as network carbides and martensite on the Stelmore air cooling line are difficult to control after further increasing the content of carbon and alloy elements, when the wire rod passes through the molten salt, the molten salt can cover the surface of the wire rod for uniform heat exchange, and the molten salt has a stronger heat exchange capacity, which can promote the rapid cooling of the wire rod. On the one hand, the temperature of the front molten salt is lower than that of the rear molten salt. When the wire rod is treated with the front molten salt, it can quickly pass through the secondary cementite precipitation temperature range of 700~800℃, avoiding the formation of secondary cementite precipitation that affects the uniform structure. On the other hand, the wire rod can quickly enter the troostite phase region from the high-temperature austenite state through ultra-high cooling rate, form a certain amount of residual austenite with large undercooling, undergo short-term martensite phase transformation, and quickly obtain partial quenched martensite. The formation of quenched martensite is more controllable and uniform, thereby further improving the strength of the steel compared with the cold-drawn pearlite steel with ferrite matrix, and also facilitates the subsequent rapid troostite phase transformation incubation, reduces the phase transformation time, and improves production efficiency.
[0017] 2. Due to the limited cooling control capacity of the Stelmor air cooling line and the continuous cooling of the wire rod, it is difficult for the troostite to undergo a full phase transformation, and the organizational stress and mechanical properties fluctuate greatly. After the wire rod is treated with the molten salt in the front section, a small amount of untransformed austenite remains in the wire rod. After passing through the molten salt in the rear section, the temperature can be raised to the troostite phase region, and the wire rod temperature is kept consistent with the molten salt temperature of the rear section. On the one hand, isothermal phase transformation can be carried out to reduce the temperature difference from the surface to the core of the wire rod, control the transformation of the untransformed high-temperature austenite in the wire rod into a troostite structure with finer interlamellar spacing, prolong the time that the wire rod is at the peak precipitation temperature of the troostite, promote the full phase transformation of the troostite structure, and increase the carbon element. It can also prevent the residual austenite from continuing to form low-temperature brittle tissue that is unfavorable to the plasticity of the tissue during the subsequent cooling process; on the other hand, the molten salt temperature of the rear-stage molten salt is higher than that of the front-stage molten salt, which can prolong the time that the wire rod is in the high temperature range, provide more thermal power for the isothermal tempering of the tissue, and promote the short-term tempering and toughening of the quenched martensite and troostite tissue formed by phase transformation, and transform the quenched martensite into tempered martensite with both strong and plastic properties, reduce the stress of the tempered troostite tissue, and then improve the matching of the strength and plasticity of the wire rod, so that the quenched martensite, which is conventionally regarded as an abnormal tissue, can be better utilized, which is beneficial to rapid offline and improved production efficiency.
[0018] 3. Due to the limited cooling control capacity of the Stelmor air-cooling line, it is difficult to bring into play the role of Nb and V elements. On the one hand, the high spinning temperature can reduce the restrictions on rolling and facilitate the induction of Nb precipitation in the rolling stage. After the wire rod is quenched and toughened at the end of the online molten salt, the wire rod is quickly cooled and the temperature difference from the surface to the core of the wire rod can be reduced. During the isothermal process of the wire rod in the later molten salt treatment, the atomic diffusion rate slows down, the nucleation rate of Nb increases, and V can form a fine and dispersed carbonitride precipitation phase, which is evenly distributed in the matrix, effectively hindering dislocation movement and improving the strength of the steel; on the other hand, the complex phase structure formed by the wire rod after isothermal tempering control undergoes a certain degree of short-term tempering. Combined with the role of Mo, the risk of carbide coarsening caused by too long a treatment time can be avoided, thereby giving full play to the strengthening and toughening role of Nb and V elements and avoiding excessive addition of micro-alloy elements to affect material costs.
[0019] The temperature of the wire rod is relatively high after the molten salt treatment in the latter stage. After slow cooling on a roller, the wire rod can be cooled too fast during the cooling process, resulting in excessive stress inside the wire rod, and promoting further toughening of the wire rod structure, thereby improving the softening effect of the wire rod, enhancing the high-strength plasticity matching of the wire rod, and reducing fluctuations in mechanical properties.
[0020] Selecting appropriate heating furnace soaking temperature and furnace time before rolling can promote the homogenization of alloy components, reduce the influence of segregation, and increase the dissolution amount of Nb and V, so that the carbonitrides of niobium and vanadium can be finely dispersed and precipitated during rolling. In the preferred technical solution, before rolling, the heating furnace soaking temperature is controlled to be 1200-1250°C, and the furnace time is 160-200min.
[0021] During the rolling, an appropriate initial rolling temperature is selected to make Nb evenly distributed in the steel, so that the austenite grains are not easy to grow during the rolling process. The matched initial rolling reduction causes the austenite to deform strongly, increases the deformation energy storage, provides more nucleation sites for Nb carbonitrides, and exerts the fine grain strengthening and precipitation strengthening effects of Nb. In the preferred technical solution, during the rolling, the initial rolling temperature is controlled to be 1040~1090℃, and the initial rolling reduction is 15%~20%.
[0022] During the rolling, appropriate final rolling temperature and final rolling reduction are selected to promote dynamic recrystallization during the final rolling process, and the grain coarsening of the wire rod during the rolling process is suppressed by the composite precipitation of Nb and V elements, and the grains are refined. In the preferred technical solution, during the rolling, the final rolling temperature is controlled to be 960~1000℃, and the final rolling reduction is 23.5%~28.5%.
[0023] In the preferred technical solution, the molten salt temperature of the front-stage molten salt is 455-480°C, and the processing time is 5-15s. The molten salt temperature of the front-stage molten salt is below the sorbite phase temperature. The lower the molten salt temperature and the longer the processing time, the more high-temperature austenite transforms to quenched martensite, and the proportion of tempered martensite in the organization increases, thereby improving the matrix strength. However, if the molten salt temperature is low and the processing time is too long, the untransformed high-temperature austenite is small, which will affect the sorbite transformation and isothermal tempering effects and cause a loss of wire rod plasticity. On the contrary, The higher the molten salt temperature and the shorter the treatment time, the less conducive it is to the quenching martensite transformation. More austenite will be transformed into troostite structure, and the matrix plasticity will increase. However, if the molten salt temperature is too high and the treatment time is too short, the quenching martensite transformation will be too little, which will obviously reduce the strength of the wire rod. Therefore, the molten salt temperature and treatment time of the front molten salt can be controlled to form a certain amount of residual austenite with large undercooling, which can promote a large part of austenite to be transformed into quenching martensite through short-time phase transformation, so as to make organizational preparation for the subsequent multiphase structure regulation and carbide control.
[0024] Since the temperature difference between the spinning temperature and the temperature of the front-stage molten salt is large, selecting a larger molten salt circulation volume can reduce the molten salt temperature rise and promote uniform phase change of the wire rod. At the same time, the larger the specification, the larger the molten salt circulation volume per unit time. In the preferred technical solution, the molten salt circulation volume of the front-stage molten salt is 400~800t / h, and the molten salt temperature rise is ≤5℃.
[0025] In the preferred technical scheme, the molten salt temperature of the rear-stage molten salt is 545~570℃, and the processing time is 160~200s. The molten salt temperature of the rear-stage molten salt is in the troostite phase region and the dispersion precipitation temperature range of V-containing carbides. The lower the molten salt temperature, the more favorable it is to the troostite lamellar separation, and it can provide more power for the dispersion precipitation of Nb and V carbides to improve the matrix strength. However, if the molten salt temperature is too low, it is not conducive to the short-time tempering of the complex phase structure and will lose the plasticity. On the contrary, the higher the molten salt temperature, the more thermal power can be provided for the isothermal tempering of the quenched martensite and troostite, and the plasticity of the wire rod can be improved. However, if the molten salt temperature is too high, the spacing between the troostite lamellar layers is larger, the softening of the wire rod is accelerated, and there is a risk of carbide precipitation and coarsening, which is not conducive to the control of strength and plasticity. The longer the processing time of the rear-stage molten salt, the more it can promote Nb and V carbides are fully precipitated, improving the softening effect of the complex phase structure and improving the strength-plasticity matching of the wire rod. However, if the processing time is too long, there is a risk of carbide precipitation and coarsening, and at the same time, the production energy consumption is increased, which is not conducive to rapid offline production and the strength-plasticity performance of the wire rod. On the contrary, the shorter the processing time, the lower the isothermal tempering effect, the lower the plasticity of the wire rod, and the lower the energy consumption. However, if the processing time is too short, there will be greater brittleness and stress in the wire rod, and Nb and V carbides will not have time to be fully precipitated, which will cause the loss of wire rod strength and significantly affect the plasticity of the wire rod. Therefore, the molten salt temperature and processing time of the latter molten salt can be further controlled to control the transformation of the high-temperature austenite of the wire rod into troostite. At the same time, after isothermal tempering, the formed complex phase structure is controlled to undergo a certain degree of short-term tempering to control the precipitation and growth of carbides and improve the strength-plasticity matching of the wire rod.
[0026] After the wire rod is treated with the molten salt in the front section, the temperature of the wire rod is quickly reduced. The molten salt in the rear section uses a lower molten salt circulation volume to control the molten salt temperature rise and reduce production energy consumption. In the preferred technical solution, the molten salt circulation volume of the rear section molten salt is 200~450t / h, and the molten salt temperature rise is ≤3℃.
[0027] The roller slow cooling can adopt an appropriate cooling speed to control the wire rod to slowly cool down, avoid the increase of wire rod stress due to too fast cooling speed, promote further toughening of wire rod structure, avoid the influence of too slow cooling speed on wire rod offline time, and promote rapid production of wire rod. In the preferred technical scheme, the roller slow cooling controls the wire rod to slowly cool down to below 250°C at a cooling speed of 0.5~0.75°C / s.
[0028] A 2500MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables, wherein the hot-rolled wire rod is manufactured by any of the above-mentioned methods for manufacturing the 2500MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables.
[0029] The hot-rolled wire rod is designed with Nb-V-Mo chemical composition and combined with online molten salt end quenching and toughening technology. The microstructure formed is different from the ferrite matrix cold-drawn pearlite steel, but a complex phase structure including tempered martensite and tempered troostite. The network carbide is effectively controlled. In the solid phase transformation process, the quenched martensite structure is formed by short-term quenching in a shear manner. The quenched martensite has higher strength than the pearlite structure. After isothermal tempering, the distortion and dislocation density are improved, the plasticity is increased, and it is transformed into a tempered martensite structure that is both strong and tough; the interlamellar spacing of the troostite structure is finer than that of the pearlite structure, and the strength and drawing hardening ability are better. After isothermal tempering, the organizational stress is greatly improved and transformed into a tempered troostite structure with better plasticity. The Nb and V elements are used to provide a strong precipitation strengthening effect, and the Mo element is used to inhibit the coarsening of the strengthening phase, so that the hot-rolled wire rod with a complex phase structure has high strength and plasticity and better organizational uniformity.
[0030] The greater the proportion of the tempered martensite, the higher the matrix strength. In a preferred technical solution, the volume percentage of the tempered martensite is 68% to 73%.
[0031] The finer the interlamellar spacing of the tempered troostite, the higher the matrix strength. In a preferred technical solution, the interlamellar spacing of the tempered troostite is 70-100 nm.
[0032] In the preferred technical solution, the network carbide level of the hot-rolled wire rod is level 0, which can make the matrix structure more continuous and eliminate weak links caused by the network carbides. When impacted by external forces, it can better absorb energy, show higher toughness, and reduce the risk of brittle fracture in subsequent drawing processes.
[0033] Since the network carbide of the wire rod is effectively improved, the austenite structure is fully and evenly transformed, and the carbide strengthening phase is dispersed and precipitated, the fluctuation of the mechanical properties of the wire rod can be further reduced, and the risk of wire breakage can be reduced. In the preferred technical solution, the mechanical property difference of the hot-rolled wire rod is ≤50MPa.
[0034] In the preferred technical solution, the diameter of the hot-rolled wire rod is 9.0~16.0mm, the tensile strength is 1710~1750MPa, and the cross-sectional shrinkage rate is 25%~30%. The hot-rolled wire rod has high strength and good plasticity, which is beneficial to improving the strength grade of the bridge cable and reducing the risk of wire breakage during drawing and torsion.
[0035] Compared with the prior art, the beneficial effects of the present invention are at least: (1) In view of the current situation that it is difficult to control the deterioration of the wire rod structure and insufficient strength and plasticity after the carbon and alloy elements of cold-drawn pearlite steel are increased, the present invention combines the high carbon chemical composition design of Nb-V-Mo with the online molten salt end quenching toughening technology to control the wire rod to quickly enter the troostite phase region from the high-temperature austenite state at an ultra-high cooling rate, form a certain amount of large undercooling residual austenite, and undergo a short-term martensite phase transformation, and then control the wire rod to enter the troostite phase region for isothermal phase transformation, control the untransformed high-temperature austenite of the wire rod to transform into troostite, and at the same time, after isothermal tempering, control the formed complex phase structure to undergo a certain degree of short-term tempering to control the precipitation of carbides, and finally roller slow cooling to promote further toughening of the wire rod structure, which can realize the regulation of complex phase structure, improve the strength and plasticity matching of the wire rod, reduce the fluctuation of the mechanical properties of the wire rod, and is conducive to controlling material costs and improving production efficiency, and has good industrial adaptability.
[0036] (2) In view of the current situation that the base material of the hot-rolled wire rod for bridge cables is insufficient in strength and plasticity and the uniformity of the structure is poor, which leads to an increased risk of wire breakage during downstream cold drawing and subsequent processing, the microstructure formed by the hot-rolled wire rod of the present invention includes a complex phase structure of tempered martensite and tempered troostite, which can effectively avoid the formation of network carbides by the C element and transform the quenched martensite into tempered martensite with both strength and plasticity, thereby maximizing the strengthening effect of the carbon element, using Nb and V elements to provide a strong precipitation strengthening effect, and using Mo element to prevent the coarsening of the precipitate phase, thereby improving the overall strength and plasticity of the wire rod, and achieving a product tensile strength of 1710~1750MPa and a cross-sectional shrinkage of 25%~30%. It is used in the manufacture of 2500MPa ultra-high strength bridge cables and other application fields, which is beneficial to reducing the risk of wire breakage and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 is a metallographic structure diagram of Example 1 of the present invention; Figure 2 is the metallographic structure diagram of Example 2 of the present invention; Figure 3 It is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION
[0038] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention, so as to propose the best way to implement the present invention, and are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention, but cannot be understood as any limitation on the scope of the present invention, which is limited only by the appended claims; the organization and performance testing of the hot-rolled wire rods obtained in the following embodiments and comparative examples include: the tensile test is carried out using "GB-T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method" to obtain the tensile strength and cross-sectional reduction rate; the organization test is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, take the overlap area position as the base point, divide each circle of wire rod into 8 sections on average, take 1 tensile specimen on each section, and the strength extreme difference of the tensile specimen after the tensile test is the mechanical property same circle difference. Embodiment 1:
[0039] A preferred embodiment of the manufacturing method of the 2500MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.98%, Si: 1.1%, Mn: 0.75%, Cr: 0.49%, Nb: 0.04%, V: 0.045%, Mo: 0.44%, P: 0.011%, S: 0.015%, and the rest are Fe and unavoidable impurities; the manufacturing method thereof is manufactured according to the process flow of rolling → spinning → online molten salt end quenching and toughening treatment → roller slow cooling → coiling, specifically: The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, promote the homogenization of alloy components, reduce segregation, and increase the dissolution of Nb and V. After the steel billet leaves the heating furnace, it is rolled into a wire with a diameter of 12mm through a rolling line, and a suitable rolling temperature and deformation amount are selected to induce Nb precipitation, promote dynamic recrystallization, refine grains, and strengthen the matrix during the final rolling process. Specifically: control the heating furnace to heat evenly The temperature is 1220℃, the time in the furnace is 185min, the initial rolling temperature is 1060℃, the initial rolling reduction is 18.5%, the final rolling temperature is 970℃, and the final rolling reduction is 27%; the wire-spinning process is used to make the wire rods coming out of the rolling line into wire rods through the wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers, so that the wire rods are in a high-temperature austenite state, which promotes the uniform and fine austenite, and provides favorable conditions for the subsequent short-term and rapid phase transformation of martensite. Specifically: the wire-spinning temperature is controlled to be 940℃.
[0040] The online molten salt terminal quenching and toughening treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first salt bath tank for the front molten salt treatment, so that the wire rod is cooled at a cooling rate of 39°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to below the sorbite phase region, forming a certain amount of large undercooling residual austenite, undergoing a short-time martensitic phase transformation, and promoting the transformation of part of the austenite structure to quenched martensite. After that, the wire rod is conveyed by a roller through the second salt bath tank for the rear molten salt treatment, and the wire rod is controlled to enter the sorbite phase region for Isothermal phase transformation is carried out to control the transformation of untransformed high-temperature austenite into troostite, promote the dispersion and precipitation of large amounts of niobium and vanadium carbides, and inhibit the growth of carbide strengthening phases. At the same time, after isothermal tempering, the formed complex phase structure is controlled to undergo a certain degree of short-term tempering to improve the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature of the front section is 461°C, the processing time is 12s, the molten salt circulation volume is 580t / h, and the molten salt temperature rise is ≤5°C; the molten salt temperature of the rear section is 551°C, the processing time is 185s, the molten salt circulation volume is 310t / h, and the molten salt temperature rise is ≤3°C.
[0041] The roller slow cooling process adopts an open insulation cover, and the wire rod passing through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from cooling too fast during the cooling process, resulting in increased stress, promoting further toughening of the wire rod structure, and improving the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 241°C at a cooling rate of 0.53°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 1 shown.
[0042] Comparative Example 1: A method for manufacturing a hot-rolled wire rod, which differs from Example 1 in that: the heating furnace soaking temperature is controlled to be 1150°C, the furnace time is 230min, the initial rolling temperature is 1000°C, the final rolling temperature is 880°C, the spinning temperature is 850°C, the wire rod is cooled at a cooling rate of 31°C / s during the front-stage molten salt treatment, and the hot-rolled wire rod is obtained after it is off the line. Embodiment 2:
[0043] A preferred embodiment of the manufacturing method of the 2500MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.97%, Si: 1.25%, Mn: 0.65%, Cr: 0.4%, Nb: 0.042%, V: 0.045%, Mo: 0.44%, P: 0.013%, S: 0.012%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt end quenching and toughening treatment → roller slow cooling → coiling, specifically: The rolling process is used to heat a steel billet with a specification of 180mm×180mm through a heating furnace to achieve a high-temperature steel billet that can be rolled into plasticity, promote the homogenization of alloy components, reduce segregation, and increase the dissolution of Nb and V. After the steel billet leaves the heating furnace, it is rolled into a wire with a diameter of 9mm through a rolling line, and a suitable rolling temperature and deformation amount are selected to induce Nb precipitation, promote dynamic recrystallization, refine grains, and strengthen the matrix during the final rolling process. Specifically: control the heating furnace to heat evenly The temperature is 1200℃, the time in the furnace is 200min, the initial rolling temperature is 1040℃, the initial rolling reduction is 20%, the final rolling temperature is 960℃, and the final rolling reduction is 28.5%; the wire-spinning process is used to make the wire rods coming out of the rolling line into wire rods through a wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers, so that the wire rods are in a high-temperature austenite state, which promotes the uniform and fine austenite, and provides favorable conditions for the subsequent short-term and rapid martensite phase transformation. Specifically: the wire-spinning temperature is controlled to be 925℃.
[0044] The online molten salt terminal quenching and toughening treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first salt bath tank for the front molten salt treatment, so that the wire rod is cooled at a cooling rate of 38°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to below the sorbite phase region, forming a certain amount of large undercooling residual austenite, undergoing a short-time martensitic phase transformation, and promoting the transformation of part of the austenite structure to quenched martensite. After that, the wire rod is conveyed by a roller through the second salt bath tank for the rear molten salt treatment, and the wire rod is controlled to enter the sorbite phase region Isothermal phase transformation is carried out to control the transformation of untransformed high-temperature austenite into troostite, promote the dispersion and precipitation of large amounts of niobium and vanadium carbides, and inhibit the growth of carbide strengthening phases. At the same time, after isothermal tempering, the formed complex phase structure is controlled to undergo a certain degree of short-term tempering to improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front section is 480°C, the processing time is 5s, the molten salt circulation volume is 400t / h, and the molten salt temperature rise is ≤5°C; the molten salt temperature of the rear section is 570°C, the processing time is 160s, the molten salt circulation volume is 200t / h, and the molten salt temperature rise is ≤3°C.
[0045] The roller slow cooling process adopts an open insulation cover, and the wire rod passing through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from cooling too fast during the cooling process, resulting in increased stress, promoting further toughening of the wire rod structure, and improving the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 229°C at a cooling rate of 0.75°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.
[0046] Comparative Example 2: A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 2 in that: during the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 37°C / s, the molten salt temperature of the front-stage molten salt is 505°C, and the hot-rolled wire rod is obtained after it comes off the line.
[0047] Comparative Example 3: A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that: during the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 39°C / s, the molten salt temperature of the front-stage molten salt is 450°C, the treatment time is 20s, and the hot-rolled wire rod is obtained after going offline. Embodiment 3:
[0048] A preferred embodiment of the manufacturing method of the 2500MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.97%, Si: 1.23%, Mn: 0.85%, Cr: 0.55%, Nb: 0.044%, V: 0.036%, Mo: 0.4%, P: 0.015%, S: 0.012%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt end quenching and toughening treatment → roller slow cooling → coiling, specifically: The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, promote the homogenization of alloy components, reduce segregation, and increase the dissolution of Nb and V. After the steel billet leaves the heating furnace, it is rolled into a wire with a diameter of 16mm through a rolling line, and a suitable rolling temperature and deformation amount are selected to induce Nb precipitation, promote dynamic recrystallization, refine grains, and strengthen the matrix during the final rolling process. Specifically: control the heating furnace to heat evenly The temperature is 1250℃, the time in the furnace is 160min, the initial rolling temperature is 1090℃, the initial rolling reduction is 15%, the final rolling temperature is 1000℃, and the final rolling reduction is 23.5%; the wire-spinning process is used to make the wire rods coming out of the rolling line into wire rods through the wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers, so that the wire rods are in a high-temperature austenite state, which promotes the uniform and fine austenite, and provides favorable conditions for the subsequent short-term and rapid phase transformation of martensite. Specifically: the wire-spinning temperature is controlled to be 970℃.
[0049] The online molten salt terminal quenching and toughening treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 40°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to below the sorbite phase region, forming a certain amount of large undercooling residual austenite, undergoing a short-time martensitic phase transformation, and promoting the transformation of part of the austenite structure to quenched martensite. After that, the wire rod is conveyed by a roller through the second stage salt bath tank for the rear stage molten salt treatment, and the wire rod is controlled to enter the sorbite phase region Isothermal phase transformation is carried out to control the transformation of untransformed high-temperature austenite into troostite, promote the dispersion and precipitation of large amounts of niobium and vanadium carbides, and inhibit the growth of carbide strengthening phases. At the same time, after isothermal tempering, the formed complex phase structure is controlled to undergo a certain degree of short-term tempering to improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front section is 473°C, the processing time is 9s, the molten salt circulation volume is 800t / h, and the molten salt temperature rise is ≤5°C; the molten salt temperature of the rear section is 562°C, the processing time is 175s, the molten salt circulation volume is 450t / h, and the molten salt temperature rise is ≤3°C.
[0050] The roller slow cooling process adopts an open insulation cover, and the wire rod passing through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from cooling too fast during the cooling process, resulting in increased stress, promoting further toughening of the wire rod structure, and improving the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 237°C at a cooling rate of 0.62°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 3 shown.
[0051] Comparative Example 4: A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the molten salt temperature of the rear-stage molten salt is 585° C., the processing time is 230 s, and the hot-rolled wire rod is obtained after going offline.
[0052] Comparative Example 5: A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the molten salt temperature of the rear-stage molten salt is 525° C., the processing time is 100 s, and the hot-rolled wire rod is obtained after going offline. Embodiment 4:
[0053] A preferred embodiment of the manufacturing method of the 2500MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.95%, Si: 1.05%, Mn: 0.82%, Cr: 0.6%, Nb: 0.048%, V: 0.035%, Mo: 0.5%, P: 0.013%, S: 0.012%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt end quenching and toughening treatment → roller slow cooling → coiling, specifically: The rolling process is used to heat a steel billet with a specification of 220 mm×220 mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, promote the homogenization of alloy components, reduce segregation, and increase the dissolution of Nb and V. After the steel billet leaves the heating furnace, the steel billet is rolled into a wire with a diameter of 15 mm through a rolling line, and a suitable rolling temperature and deformation amount are selected to induce Nb precipitation, promote dynamic recrystallization during the final rolling process, refine grains, and strengthen the matrix. Specifically: control the uniformity of the heating furnace The heating temperature is 1235°C, the furnace time is 175min, the initial rolling temperature is 1075°C, the initial rolling reduction is 16%, the final rolling temperature is 985°C, and the final rolling reduction is 25%; the wire-spinning process is used to turn the wire rods coming out of the rolling line into wire rods through a wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers, so that the wire rods are in a high-temperature austenite state, which promotes uniform and fine austenite, and provides favorable conditions for the subsequent short-term and rapid martensite phase transformation. Specifically: the wire-spinning temperature is controlled to be 955°C.
[0054] The online molten salt terminal quenching and toughening treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first salt bath tank for the front molten salt treatment, so that the wire rod is cooled at a cooling rate of 41°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to below the sorbite phase region, forming a certain amount of large undercooling residual austenite, undergoing a short-time martensitic phase transformation, and promoting the transformation of part of the austenite structure to quenched martensite. After that, the wire rod is conveyed by a roller through the second salt bath tank for the rear molten salt treatment, and the wire rod is controlled to enter the sorbite phase region for Isothermal phase transformation is carried out to control the transformation of untransformed high-temperature austenite into troostite, promote the dispersion and precipitation of large amounts of niobium and vanadium carbides, and inhibit the growth of carbide strengthening phases. At the same time, after isothermal tempering, the formed complex phase structure is controlled to undergo a certain degree of short-term tempering to improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front section is 455°C, the processing time is 15s, the molten salt circulation volume is 710t / h, and the molten salt temperature rise is ≤5°C; the molten salt temperature of the rear section is 545°C, the processing time is 200s, the molten salt circulation volume is 400t / h, and the molten salt temperature rise is ≤3°C.
[0055] The roller slow cooling process uses an open insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from cooling too fast during the cooling process, which leads to increased stress, promotes further toughening of the wire rod structure, and improves the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 245°C at a cooling rate of 0.5°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage.
[0056] Comparative Example 5: A method for manufacturing a hot-rolled wire rod, the manufacturing method differs from Example 4 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt terminal quenching and toughening treatment → air cooling → coiling, the air cooling is carried out by opening the insulation cover, and the wire rod is transported through the second salt bath tank by a conveyor roller, and the wire rod is controlled to be slowly cooled to 240°C at a cooling rate of 1.3°C / s. After the hot-rolled wire rod is off the line, the tensile strength of the hot-rolled wire rod is 1761MPa, the cross-sectional shrinkage rate is 23%, and the mechanical property same-circle difference is 57MPa.
[0057] The hot rolled wire rods obtained in the above examples 1 to 4 and comparative examples 1 to 5 were subjected to microstructure and performance testing, and the comparative results obtained are shown in Table 1 below: Table 1. Comparison of microstructure and performance of hot rolled wire rods with different compositions and manufacturing methods
[0058] It can be seen from the results of Examples 1 to 4 that the Nb-V-Mo chemical composition design is combined with the online molten salt end quenching and toughening technology design, the wire rod is controlled to quickly enter the troostite phase region from the high-temperature austenite state at an ultra-high cooling rate for a short-term martensite phase transformation, the wire rod is controlled to enter the troostite phase region for isothermal phase transformation and short-time tempering, and the roller is slowly cooled and toughened to form a microstructure including a complex phase structure composed of tempered troostite and tempered martensite, which can improve the strength and plasticity matching of the wire rod, and the deterioration of the wire rod organization is effectively controlled, so that the product tensile strength is 1710~1750MPa and the cross-sectional shrinkage rate is 25%~30%.
[0059] From the comparison results of Example 1 and Comparative Example 1, it can be seen that by selecting an appropriate spinning temperature, it is possible to avoid the spinning temperature being too low to limit rolling control and to avoid the formation of network carbides in the spinning stage, thereby providing favorable conditions for the subsequent molten salt end quenching to promote the short-term martensite phase transformation.
[0060] From the comparison results of Example 2 and Comparative Example 2, it can be seen that the higher the molten salt temperature of the front stage molten salt and the shorter the treatment time, it is not conducive to the quenching martensite transformation, more austenite will be transformed into troostite structure, and the matrix plasticity will increase. However, if the molten salt temperature is too high and the treatment time is too short, the quenching martensite transformation is too little, which will obviously lose the strength of the wire rod.
[0061] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the lower the molten salt temperature of the front-stage molten salt and the longer the treatment time, the more the high-temperature austenite is transformed into quenched martensite, the proportion of tempered martensite in the organization increases, and the matrix strength is improved. However, the molten salt temperature is low and the treatment time is too long, and the untransformed high-temperature austenite is small, which will affect the troostite transformation and isothermal tempering effect, and lose the plasticity of the wire rod.
[0062] From the comparison results of Example 3 and Comparative Example 4, it can be seen that the higher the molten salt temperature of the rear-stage molten salt and the longer the treatment time, more thermal power can be provided for the isothermal tempering of quenched martensite and troostite, thereby promoting the improvement of the plasticity of the wire rod. However, if the molten salt temperature is too high and the treatment time is too long, the spacing between the troostite lamellae is large, the wire rod softens faster, and there is a risk of carbide precipitation and coarsening, which is not conducive to the control of strength and plasticity.
[0063] From the comparison results of Example 3 and Comparative Example 5, it can be seen that the lower the molten salt temperature of the latter molten salt, the more favorable it is to the sorbite lamellar tomography, which can provide more power for the dispersion and precipitation of Nb and V carbides to improve the matrix strength. However, if the molten salt temperature is too low and the treatment time is too short, it is not conducive to the short-term tempering of the multiphase structure, and greater brittleness and stress remain in the wire rod. Nb and V carbides will not have time to fully precipitate, which will result in a loss of wire rod strength and a significant impact on the plasticity of the wire rod.
[0064] From the comparison results of Example 4 and Comparative Example 6, it can be seen that the roller slow cooling adopts an appropriate cooling rate to control the slow cooling of the wire rod, avoid the increase of wire rod stress due to excessive cooling rate, and promote further toughening of the wire rod structure.
[0065] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for manufacturing a 2500MPa grade high-strength multiphase hot-rolled wire rod for bridge cables, characterized in that: The manufacturing method thereof comprises: The hot-rolled wire rod is rolled to produce a wire rod according to its chemical composition, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.95% to 0.98%, Si: 1.05% to 1.25%, Mn: 0.65% to 0.85%, Cr: 0.40% to 0.60%, Nb: 0.04% to 0.048%, V: 0.035% to 0.045%, Mo: 0.40% to 0.50%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable Impurities; After the wire is spun into a wire rod at a spinning temperature of ≥925°C, it is subjected to an online molten salt terminal quenching and toughening treatment, so that the wire rod first passes through the front section of molten salt and is cooled at a cooling rate of ≥38°C / s, and part of the austenite structure is transformed into quenched martensite, and then is heated to the bainite phase region temperature through the rear section of molten salt, and the untransformed austenite is controlled to be transformed into bainite and isothermally tempered, and the precipitation and growth of carbides are controlled, and finally it is slowly cooled through a roller to be made into a hot-rolled wire rod with a microstructure including a complex phase structure composed of tempered martensite and tempered bainite.
2. The method for manufacturing 2500MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: Before the rolling, the soaking temperature of the heating furnace is controlled to be 1200-1250° C., and the time in the furnace is 160-200 minutes.
3. The method for manufacturing 2500MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: During the rolling, the initial rolling temperature is controlled to be 1040-1090° C., the initial rolling reduction is 15%-20%, the final rolling temperature is controlled to be 960-1000° C., and the final rolling reduction is controlled to be 23.5%-28.5%.
4. The method for manufacturing 2500MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: The molten salt temperature of the front-stage molten salt is 455-480° C., and the processing time is 5-15 seconds; the molten salt temperature of the rear-stage molten salt is 545-570° C., and the processing time is 160-200 seconds.
5. The method for manufacturing 2500MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 4, characterized in that: The molten salt circulation volume of the front-stage molten salt is 400-800 t / h, and the molten salt temperature rise is ≤5°C; the molten salt circulation volume of the rear-stage molten salt is 200-450 t / h, and the molten salt temperature rise is ≤3°C.
6. The method for manufacturing 2500MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 4, characterized in that: The roller slow cooling controls the wire rod to be slowly cooled to below 250° C. at a cooling rate of 0.5-0.75° C. / s.
7. A 2500MPa grade high-strength multiphase hot-rolled wire rod for bridge cables, characterized in that: The hot-rolled wire rod is manufactured by the method for manufacturing 2500MPa-grade high-strength multi-phase hot-rolled wire rod for bridge cables as described in any one of claims 1 to 6.
8. The 2500MPa high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 7, characterized in that: The volume percentage of the tempered martensite is 68% to 73%, and the interlamellar spacing of the tempered troostite is 70 to 100 nm.
9. The 2500MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 7, characterized in that: The network carbide grade of the hot-rolled wire rod is grade 0, and the mechanical property difference is ≤50MPa.
10. The 2500MPa high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 7, characterized in that: The hot-rolled wire rod has a diameter of 9.0-16.0 mm, a tensile strength of 1710-1750 MPa, and a cross-sectional shrinkage of 25%-30%.
Citation Information
Patent Citations
Steel wire rod, heat treatment method and production method of steel wire rod and galvanized steel wire
CN114032372A
Production method of wire rod for high-strength bridge cable galvanized steel wire
CN115430705A
Cold heading steel wire rod for 14.9-grade non-quenched and tempered bolt and manufacturing method of cold heading steel wire rod
CN118653095A
High-strength complex-phase hot-rolled wire rod for 2060 MPa bridge cable and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN119162429A
High-strength complex-phase hot-rolled wire rod for 2200 MPa bridge cable and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN119662951A
Cited By
1450MPa-grade high-strength tool steel wire rod and manufacturing method thereof
CN120591518A
1350MPa-grade high-strength tool steel wire rod and manufacturing method thereof
CN120608191A
A 1350mpa grade high strength tool steel wire rod and a manufacturing method thereof
CN120608191B
Hot-rolled wire rod for 2230 MPa grade stranded wire and manufacturing method of hot-rolled wire rod
CN121046731A
Heat treatment method of gear
CN121320707A